The association between fracture site and obesity in men: a population-based cohort study. - Premaor, M; Compston, J; Fina Avilés, F; Pagès-Castellà, A; Nogués, X; Díez-Pérez, A; Prieto-Alhambra, D (2013)
A site-dependent association between obesity and fracture has been reported in postmenopausal women. In this study we investigated the relationship between body mass index (BMI) and fracture at different skeletal sites in older men (≥65 years). We carried out a population-based cohort study using data from the Sistema d'Informació per al Desenvolupament de l'Investigació en Atenció Primària (SIDIAP(Q) ) database. SIDIAP(Q) contains the primary care and hospital admission computerized medical records of >1300 general practitioners (GPs) in Catalonia (Northeast Spain), with information on a representative 30% of the population (>2 million people). In 2007, 186,171 men ≥65 years were eligible, of whom 139,419 (74.9%) had an available BMI measurement. For this analysis men were categorized as underweight/normal (BMI < 25 kg/m(2) , n = 26,298), overweight (25 ≤ BMI < 30 kg/m(2) , n = 70,851), and obese (BMI ≥ 30 kg/m(2) , n = 42,270). Incident fractures in the period 2007 to 2009 were ascertained using International Classification of Diseases, 10th edition (ICD-10) codes. A statistically significant reduction in clinical spine and hip fractures was observed in obese (relative risk [RR], 0.65; 95% confidence interval [CI], 0.53-0.80 and RR, 0.63; 95% CI, 0.54-0.74, respectively), and overweight men (RR, 0.77; 95% CI, 0.64-0.92 and RR, 0.63; 95% CI 0.55-0.72, respectively) when compared with underweight/normal men. Additionally, obese men had significantly fewer wrist/forearm (RR, 0.77; 95% CI, 0.61-0.97) and pelvic (RR, 0.44; 95% CI, 0.28-0.70) fractures than underweight/normal men. Conversely, multiple rib fractures were more frequent in overweight (RR, 3.42; 95% CI, 1.03-11.37) and obese (RR, 3.96; 95% CI, 1.16-13.52) men. In this population-based cohort of older men, obesity was associated with a reduced risk of clinical spine, hip, pelvis, and wrist/forearm fracture and increased risk of multiple rib fractures when compared to normal or underweight men. Further work is needed to identify the mechanisms underlying these associations.